Hubungan Motivasi Kerja Terhadap Kinerja Pegawai Badan Keluarga Berencana Daerah (Bkbd) Kecamatan Ulu Musi Kabupaten Empat Lawang - Alesandro, Cixo; Irwanto , Tito; Febliansa, M. Rahman (Jurnal Bisnis, Manajemen dan Akuntansi, 2025)
Motivation is an impetus that arises from within an individual to carry out the tasks assigned. Motivation is very important in achieving employee performance. This study aims to determine the relationship of work motivation to employee performance at the Office of the Badan Keluarga Berencana Daerah (BKBD) of Ulu Musi District, Empat Lawang Regency. The data collection method in this study was to use a questionnaire and the analysis method was simple regression. The sample of this study amounted to 22 people.Based on the results of research and discussion, it is found that work motivation has a significant effect on employee performance at the Office of the Badan Keluarga Berencana Daerah (BKBD) of Ulu Musi District, Empat Lawang Regency. From the results of the Product Moment Correlation r test, it shows that there is a real and significant relationship between motivation and employee performance of 0.832 or 69.22%. The coefficient interval of 0.800 - 1.000 means that the level of relationship between work motivation and employee performance is very strong. The results of hypothesis testing with the t-test formulation show t- count> t-table, where: 2,962 > 1,720.In this study the authors provide advice to the Office of the Badan Keluarga Berencana Daerah (BKBD) of Ulu Musi District, Empat Lawang Regency in order to improve performance and productivity, it is necessary to have constructive and continuous motivation. Motivation does not always have to be material and financial, but motivation can be in the form of attention, encouragement of appreciation and praise which is no less important.